Host - Bacterial Pathogen Communication: The Wily Role of the Multidrug Efflux Pumps of the MFS Family - Pasqua, Martina; Bonaccorsi di Patti, Maria Carmela; Fanelli, Giulia; Utsumi, Ryutaro; Eguchi, Yoko; Trirocco, Rita; Prosseda, Gianni; Grossi, Milena; Colonna, Bianca (Frontiers in Molecular Biosciences, 2021)
Bacterial pathogens are able to survive within fundamentally diverse habitats. The dynamic adaptation to the surroundings depends on their ability to sense environmental variations and to respond in an appropriate manner. This involves, among others, the activation of various cell-to-cell communication strategies. The capability of the bacterial cells to rapidly and co-ordinately set up a fruitful interplay with the host cells and/or with other bacteria facilitates their survival in the new niche. Efflux pumps are ubiquitous transmembrane transporters, able to extrude a large set of different molecules. They are strongly implicated in antibiotic resistance since they are able to efficiently expel most of the clinically relevant antibiotics from the bacterial cytoplasm. Besides antibiotic resistance, multidrug efflux pumps take part in several relevant processes of bacterial cell physiology, including cell to cell communication, and contribute to increase the virulence potential of several bacterial pathogens. Here, we focus on the structural and functional role of multidrug efflux pumps belonging to the Major Facilitator Superfamily (MFS), the largest family of transporters, highlighting their involvement in the colonization of host cells, in virulence and in biofilm formation. We will offer an overview on how MFS multidrug transporters contribute to bacterial survival, adaptation and pathogenicity through the export of diverse molecules. This will be done by presenting the functions of several relevant MFS multidrug efflux pumps in human life-threatening bacterial pathogens as Staphylococcus aureus, Listeria monocytogenes, Klebsiella pneumoniae, Shigella flexneri, Acinetobacter baumannii.